The new way of triathlon preparation in youth athletes - Papai, Zsofia; Wilhelm, Marta; Szakaly, Zsolt (Journal of Physical Education and Sport, 2022)
The aim of our research was to find a way, based on international experience, to examine the training method that can be successfully used in youth age groups, and as a consequence, to increase the effectiveness of the sport of triathlon. In Hungary, the methods of preparing the younger age group (10-18 y) are not yet uniform. Hungarian triathletes do not dominate at the international level, neither in the junior age groups nor in the elite field. Two basic methods "fight" each other in Hungary, the so-called "threshold" training (training at the anaerobic threshold), the effectiveness of which has been proven by numerous studies in various sports. The aim of this study was to analyze the effectiveness of "Polarized" (Pol) and "Threshold" (TR) training in youth ages (15-18y). Male youth triathlete subjects taking part in systematic training (n=10, n(Pol)=5; n(TR)=5) were studied. Performance (time), physiological data from spiroergometry (vita maxima) tests and anthropometric features were measured in this longitudinal study (3 years). Performance improvement, relative oxygen uptake (rVO2max) and aerobic time significantly increased (p<0.05) in Pol group, while differences of their anthropometric features did not change significantly during the research. No significant changes were found in any parameters of TR group. There were no significant differences of anthropometric and cardiovascular (Heart Rate) characteristics between the two groups in any assessment. The differences of rVO2max and relative aerobic capacity at the anaerobic threshold were significant in the Pol group (p<0.05) at the second and third measurements. Performance improvement and time in aerobic zone increased more in the Pol group than in the TR group (p<0.05). The Pol training method proved to be more effective than the TR training of the studied group.